Optimization of Electricity Transition Scenarios Toward Net Zero Emissions by 2060 in Indonesia: Resource Analysis and System Reliability: - Nursidik; Boer, Rizaldi; Rusli, Meika Syahbana (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
Indonesia faces a critical challenge to fulfill Indonesia's commitment to the Enhanced Nationally Determined Contribution (ENDC) 2030 and to meet the net zero greenhouse gas (GHG) emissions by 2060. This requires the electricity sector to adopt low-emission, reliable, and investment-efficient technologies. This study develops three electricity transition scenarios toward net zero emission using the Long-range Energy Alternatives Planning (LEAP) system. Three scenarios are: (1) Current Strategy (CS) with emphasis on coal-based generation with Carbon Capture and Storage (CCS); (2) Renewable Energy-Based Transition (ET) prioritizing solar, wind, hydro, and geothermal; and (3) Enhanced Renewable and New Energy Transition (EBT) combining renewables with nuclear and hydrogen baseload. Model results demonstrate that electricity demand in 2060 is projected at 1,808 TWh with peak load of 245 GW. The required generation capacity reaches 565 GW (CS), 758 GW (EBT), and 1211 GW (EBT). Peak emissions occur in 2031 at 440 MtCO₂ (CS) and 439 MtCO₂ (ET and EBT). By 2060, zero emissions are achieved in the ET and EBT scenarios, while CS still emits 103 MtCO₂. All scenarios meet the ENDC 2030 emission-reduction target. System reliability is highest in EBT and CS, whereas emission reductions are greatest in ET and EBT.